The relationship between occlusal support zones and blood glucose levels: the moderating role of carbohydrate and fiber intake frequency - Rakasiwi, Arfita Ajeng Dewi; Amalia, Rosa; Priyono, Bambang (MKGK (Majalah Kedokteran Gigi Klinik) (Clinical Dental Journal) UGM, 2024)
Blood glucose levels are influenced by carbohydrate and fiber intake. A diet high in carbohydrates and low in fiber can elevate blood glucose levels. The impact of carbohydrate and fiber intake is mediated by masticatory function, which depends on the occlusal contact of the posterior teeth. The aim of this study was to examine the relationship between the occlusal support zone and blood glucose levels, with the frequency of carbohydrate and fiber consumption actingas moderating variables. This research employed an observational analytic design using a cross-sectional method. The sample consisted of 33 elderly individuals, aged 60 to 74 years, from Kalibening Village, Dukun Subdistrict, Magelang Regency, selected through accidental sampling. Blood glucose levels were measured using the Accu-Chek test, occlusal support zones were assessed with the Eichner index, and the frequency of carbohydrate and fiber intake was recorded through a 4-day food diary questionnaire. The examination data were analyzed using pathanalysis. The results of the analysis showed no significant direct relationship between the occlusal support zone and blood glucose levels (p = 0.76; r = 0.003). However, when the frequency of carbohydrate consumption was included as a moderating variable, a significant relationship was found (p = 0.008). In contrast, when the moderating variable was the frequency of fiber consumption (p = 0.97), no significant relationship was observed. The study concludes thatthere is a relationship between the occlusal support zone and blood glucose levels in the elderly, with the frequency of carbohydrate consumption as a moderating variable. However, no relationship was found between the occlusal support zone and blood glucose levels when the frequency of fiber consumption was the moderating variable.